Modified graphene oxide as an efficient magnetic adsorbent for the simultaneous removal of Sunset Yellow and Tartrazine dyes - Margan Qaed Amini Farsani; Shahla Elhami (Desalination and Water Treatment, 2024)
Magnetic Graphene Oxide-Semicarbazide (MGO-Se) was successfully fabricated and, as a new adsorbent was used for simultaneous ultrasound-assisted adsorption of Sunset Yellow (SY) and Tartrazine (Tar) dyes from aqueous samples. The characterizations of MGO-Se were studied by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Fourier-Transform Infrared spectroscopy (FT-IR). A spectrum overlapping of SY and Tar was resolved by the derivative spectrophotometric technique. The effects of variables on the removal of the dye such as pH, the dose of MGO-Se, sonication time, and initial dye concentration were studied and optimized. Under the optimized condition, the removal efficiencies were obtained by more than 92% and 91% for SY and Tar dyes (with a concentration of 50 mg L−1 for each dye), respectively. The adsorbent was successfully reused 8 times with very little change in the adsorption efficiency, which indicates that it is highly reusable. The experimental equilibrium data of SY and Tar onto MGO-Se was utilized to compare nonlinear and linear isotherm and kinetics models for parameter determination. The best models for fitting equilibrium data were Linear Langmuir and nonlinear pseudo-second-order models with lower error functions. Thermodynamic parameters predicted the exothermic nature, spontaneity, and feasibility of the adsorption process. The absorbent had a greater ability to remove dyes from real samples.